2016
DOI: 10.1111/jocs.12799
|View full text |Cite
|
Sign up to set email alerts
|

A study of the mechanical properties of ePTFE suture used as artificial mitral chordae

Abstract: The increase of the length of artificial ePTFE chordae is accompanied by an increasing stiffness that compromises the long-term resistance of the chordae. ePTFE length can alter the performance of artificial chordae. This suggests that mitral valve repairs which anchor ePTFE neochordae to the ventricular apex may have less durability than when anchored to the tips of the papillary muscles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 15 publications
0
27
0
Order By: Relevance
“…In general, it has been found that ePTFE chordae do not have similar mechanical properties to native chordae. In particular, Caimmi et al [68] found that ePTFE chordae were of higher compliance than their native counterparts, and that the stiffness of ePTFE chordae increases with the length of the implant. These findings would be beneficial to the refinement of therapeutics to better emulate native structures.…”
Section: Mechanics Of Artificial Chordaementioning
confidence: 99%
“…In general, it has been found that ePTFE chordae do not have similar mechanical properties to native chordae. In particular, Caimmi et al [68] found that ePTFE chordae were of higher compliance than their native counterparts, and that the stiffness of ePTFE chordae increases with the length of the implant. These findings would be beneficial to the refinement of therapeutics to better emulate native structures.…”
Section: Mechanics Of Artificial Chordaementioning
confidence: 99%
“…Mechanical properties derived from uniaxial tensile tests were obtained from literature. 27,28 In this study, virtual transapical neochordae repair was modeled under optimal implantation conditions, that is, following the manufacturer's recommendations 29 and the clinical step-by-step guide. 26,30 Clinically, three or four neochordae are implanted on average in order to balance the tension per neochorda, provide structural support, and avoid excessive mechanical stress on the leaflets.…”
Section: Transapical Neochordae Modelingmentioning
confidence: 99%
“…Moreover, different lengths of ePTFE materials showed different mechanical properties and could alter the performance of the material. 31 Based on the mechanical experiments in our study, both the membranes (15×30 mm) had moderate cellulose crystallinity and mechanical strength. The elastic modulus of the BC+Exos membrane and BC membrane was 11.02±0.76 and 10.98±1.26 MPa ( Figure 3E), which was close to the elastic modulus of articular cartilage.…”
Section: Properties Of the Bc+exos Membranementioning
confidence: 67%